METHODOLOGICAL BASIS OF THE USE OF DIGITAL PEDAGOGICAL TECHNOLOGIES IN TEACHING EDUCATION (Universal International Scientific Journal, 2026)
This article discusses the methodological foundations of the use of digital pedagogical technologies in the process of teaching education. It also analyzes the impact of digital technologies on the effective organization of the educational process, increasing student activity, and their spiritual and moral development.
Keywords: Digital pedagogical technologies, educational science, interactive education, information and communication technologies, multimedia tools, e-learning, innovative methods, educational effectiveness.